The Effect of Motivation, Work Discipline And Supervision on the Performance of Employees at Jati Padang Regional General Hospital - Fauzi, Achmad; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to determine how much influence motivation, work discipline and supervision have on employee performance at the Jati Padang Regional General Hospital, South Jakarta, the population in this study were 278 employees of the Jati Padang Regional General Hospital, South Jakarta. Using the formula, respondents were selected. Slovin as a sample from 278 to 74 employees, based on the results of data analysis using SPSS the results of the study showed the proposed hypothesis 3, there was a significant hypothesis 3. The data collected was then analyzed using inferential data analysis techniques with multiple linear regression and using the application of the Statistical Product and Service Solution (SPSS) version 26 program. With the results of this study, the authors hope that the Jati Padang Regional General Hospital can strive to increase motivation, Work Discipline and Supervision of Employee Performance.